KEBIJAKAN PEMERINTAH DAERAH DALAM PEMBANGUNAN SARANA DAN PRASARANA PENDIDIKAN DI KABUPATEN JAYAWIJAYA PROPINSI PAPUAKEBIJAKAN PEMERINTAH DAERAH DALAM PEMBANGUNAN SARANA DAN PRASARANA PENDIDIKAN DI KABUPATEN JAYAWIJAYA PROPINSI PAPUA - WORABAY, MENASER GASPER (Sam Ratulangi University, 2018)
Abstract: the purpose of this study is to contribute to the development of science in the field of stateadministration studies, especially for studies related to local government policy in the development ofeducational facilities and infrastructure as well as a material information and input for localgovernmentJayawijaya Regency in improving the quality of education facilities and infrastructuredevelopment.the research informants were the Bupati, the Bupati's deputy, the DPRD (Chairman ofCommission C), the Head of the Education Office, the Head of Education and Education Facility, and 6principals, totaling 11 people. Data collection is done by observation, interview and literature study. while dataanalysis using qualitative analysis technique of interactive model according to Miles and Huberman. based onthe results of data analysis concluded that the Local Government as a drafter and implementer of RegionalPolicy in the development of educational facilities and infrastructure in Jayawijaya Regency in the authorityrequired to improve the quality of education. concerning education facilities and infrastructures in JayawijayaRegency still need funding and expense big enough to reach adequate standard of education service especiallyschool children of elementary, junior high, and vocational high school. is very important educational facilitiesand infrastructure and also added with other components such as educational support facilities and educatorsin supporting the teaching and learning process to maximize the quality of education in Jayawijaya Regency.the increasing quality of education services, especially schools, is strongly influenced by the VisionaryPrincipal's care and commitment, the quality management used and the education / school organizers to providegood education / schools.Keywords: Local Government Policy, Education Facility and Infrastructure.